Electrochemical Study of Graphene Coated Nickel Foam as an Anode for Lithium-Ion Battery [Article] - Mukanova, Aliya; Nurpeissova, Arailym; Kim, Sung-Soo; Myronov, Maksym; Bakenov, Zhumabay; Zharbossyn, Assem (Eurasian Chemico-Technological Journa, 2018)
This study reports the synthesis of a few-layered graphene (GF) thin film on Ni foam by chemical vapor deposition (CVD) technique and investigation of its electrochemical performance as a negative electrode for lithium-ion batteries (LIBs). A standard deposition procedure with a methane precursor was employed to prepare the GF films. The SEM studies revealed the formation of a dark uniform film on the surface of Ni foam’s wires upon the CVD deposition. The film consisted of numerous GF sheets replicating the shape of the Ni grain boundaries over the Ni wire surface. The Raman spectroscopy of the prepared films on the Ni foam confirmed that the samples are a few-layered GF with high quality and purity. In order to evaluate the potential of the use of the prepared materials as an anode in LIBs, their electrochemical performance was studied in coin-type lithium halfcells using cyclic voltammetry (CV) and galvanostatic cycling. The results of CV showed that both graphene and native oxide layer (NiO) on nickel foam exhibit electrochemical activity with respect to lithium ions. Galvanostatic cycling revealed that both GF and NiO contribute to the overall capacity, which increases upon cycling with a stable Coulombic efficiency of around 99%. The designed 3D GF coated NiO/Ni anode demonstrated a gradual increase of its areal charge capacity from 65 μAh cm-2 at the initial cycle to 250 μAh cm-2 at the final 250th cycle.
http://ect-journal.kz/index.php/ectj/article/view/694
Keywords: graphene; nickel; 3D current collector; lithium-ion batteries; CVD